Fifteen Minutes of Left Prefrontal Repetitive Transcranial Magnetic Stimulation Acutely Increases Thermal Pain Thresholds in Healthy Adults - Jeffrey J Borckardt; Arthur R Smith; Scott T Reeves; Mitchell Weinstein; F Andrew Kozel; Ziad Nahas; Neal Shelley; R Kyle Branham; K Jackson Thomas; Mark S George (Pain Research and Management)
BACKGROUND: Transcranial magnetic stimulation (TMS) of the motor cortex appears to alter pain perception in healthy adults and in patients with chronic neuropathic pain. There is, however, emerging brain imaging evidence that the left prefrontal cortex is involved in pain inhibition in humans.